Optimization of Conditions for Human Bacterial Preparation for Biological Correction of Intestinal Microflora - Sorokina, E.A.; Zhgun, E.S.; Kislun, Yu.V.; Denisova, E.A.; Bespyatykh, Yu.A.; Ilina, E.N. (Biomedical Chemistry: Research and Methods, 2021)
Fecal microbiota transplantation (FMT) is now considered as an effective tool for the treatment of various GI pathologies. Fecal preparations are delivered both through the lower GIT (enema, colonoscopy) and upper (endoscopy, capsules). A common disadvantage of instrumental methods of administration is their high invasiveness associated with the risk of intestinal perforation and the use of anesthesia. Oral capsules are minimally invasive, comfortable and more aesthetic, so this method of drug delivery is gaining popularity. The main issue with the use of frozen feces (including the lyophilisate used in capsules) is its efficiency compared to the original material. During lyophilization, cells are exposed to stress factors such as low temperatures, water crystallization, osmotic stress, changes in pH, and dehydration. To reduce the likelihood of cell damage during lyophilization, protective media (lyo-protectants) are used. In this work sucrose, gelatin, and their combinations have been used as lyoprotectors. To estimate the number of microorganisms, a bacteriological study was carried out. The number of Bifidobacteria, Lactobacilli, and the total number of E.coli and Enterobacteriaceae was estimated. It was found that the lyophilized stool sample containing 10% sucrose as a protective medium had the highest number of viable cells. Also, the physical properties of the lyophilisate (its flowability) are convenient for preparing capsulated form. The molar ratios of short chain fatty acids (SCFAs) in the original fecal samples and lyophilisates were studied by gas chromatography. The molar ratios of major SCFAs (acetate, propionate and butyrate) were identical in the samples studied. The composition of the protective medium in which the lyophilized biomaterial corresponds to the original feces in terms of the number of "live" microorganisms has been proposed. According to its physical characteristics lyophilisate is convenient for capsules preparation.